Middle powers amid Sino-U.S. rivalry: assessing the 'good regional citizenship' of Australia and Indonesia. Issue 6 (2nd November 2022) - Teo, Sarah
Abstract: This paper argues that amid intensifying Sino-U.S. rivalry, middle powers in East Asia have contributed towards regional peaceful change through the exercise of good regional citizenship, a concept which draws on and modifies from the more commonly known good international citizenship which is closely associated with middle powers. Specifically, good regional citizenship involves proactively strengthening inclusive multilateralism, enhancing the rules-based order, and contributing to bridging efforts in East Asia. The paper examines the good regional citizenship of two middle powers, namely Australia and Indonesia. It finds that while both countries have exercised good regional citizenship, their specific strategies or the outcomes of their initiatives on regional dynamics have varied as a result of their relations with the respective major powers and their general foreign policy approaches. Australia's good regional citizenship has supported the preservation of U.S. leadership in East Asia vis-à-vis the rise of other regional powers, while Indonesia's good regional citizenship has helped to narrow the gaps among regional actors through mechanisms led by the Association of Southeast Asian Nations (ASEAN).